Large uterine leiomyoma with smooth muscle tumour of uncertain malignant potential: a case report - Chatterjee, Abhinibesh; Chatterjee, Polly; Bhadra, Avishek; Biswas, Rumela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Smooth muscle tumours of uncertain malignant potential (STUMP) are a category of uterine neoplasms that do not meet the criteria for benign or malignant tumours, potentially representing an intermediate stage between leiomyomas and leiomyosarcomas. A 26-year-old nulliparous woman presented with heavy menstrual bleeding and an abdominal mass, with preoperative imaging suggesting a benign uterine myoma. Following a laparoscopic myomectomy, histological analysis revealed STUMP, characterized by a low mitotic index and marked nuclear pleomorphism without necrosis. The patient was advised to conceive soon and plan for definitive surgery after completing her family. She later delivered via elective caesarean section at 35 weeks and is currently recovering well. STUMP often mimics benign leiomyomas and is usually diagnosed post-surgery, complicating preoperative assessment. Recurrence rates vary, particularly in younger patients, emphasizing the need for individualized management strategies that balance fertility preservation with monitoring for recurrence. Regular follow-ups are essential for optimal care.